Relationship Of Nutritional Components In Toddlers Aged 25-59 Months To Stunting And Short Stature Incidents In Pragaan District, Sumenep Regency - Conita Walida Sabrina; Pertiwi Febriana Chandrawati (Saintika Medika, 2021)
Stunting and short stature are height per-age <-2SD for specific age and gender. The process of stunting and short stature starts from the womb until the beginning of life. The direct cause of stunting is the lack of nutritional intake in the first 1000 days of life, which can inhibit height growth. Study aimed to investigate the association between the relationship of nutritional components in toddlers to stunting and short stature incidents in Pragaan District, Sumenep Regency. Observational analytic with a case-control approach, using the Purposive-Sampling method. The research sample consisted of 76 toddlers aged 25-59 months. The statistical analysis used was the chi-square test and logistic regression test. The result of chi-square test and logistic regression for stunting on nutrient intake variable ( p = 0.000, OR = 26,3, CI 95% (4,630-153,573), history of breastfeeding (p=0,000, OR=72,6,CI95% (7,63-690,78), iodized salt (p=0,000, OR=8,5,CI 95% (1,833-39,421), FE tablet (p=0,000,OR=37,00, CI 95%(3,762-363,91). The result of chi-square test and logistic regression for short stature on nutrient intake variable (p=0.001, OR=7,2,CI 95% (2,260-23,400), history of breast feeding (p=0,007, OR=4,500,CI 95% (1,210-16,742), iodized salt (p=0,007, OR=19,125, CI 95% (5,062-72,259), FE tablet (p=0,149). There is a relationship between nutritional components intakes such as breastfeeding history and iodine salt consumption with stunting and short stature in Pragaan District, Sumenep Regency.